2015
DOI: 10.1097/acm.0000000000000617
|View full text |Cite
|
Sign up to set email alerts
|

Differences Between Attendings’ and Fellows’ Perceptions of Futile Treatment in the Intensive Care Unit at One Academic Health Center

Abstract: Purpose Knowing when patients are too ill to benefit from intensive care is essential for clinicians to recommend aggressive or palliative care as appropriate. To explore prognostic ability among critical care fellows, the authors compared fellows’ and attendings’ assessments of futile critical care and evaluated factors associated with assessments. Method Thirty-six attendings and 14 fellows in intensive care units at the University of California, Los Angeles, were surveyed daily for 3 months (December 2011… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 14 publications
0
18
0
Order By: Relevance
“…This is illustrated by an online survey with open questions among 592 patients and relatives in the Netherlands which found that following the patient’s, as well as relatives’ wish, was commonly mentioned to describe appropriate care [ 64 ]. It was also notable that it can be considered appropriate when patient or family/guardian understands that a treatment is unlikely to succeed but chooses to attempt a curative or life-prolonging treatment anyway [ 64 66 ] ( n = 3). For instance, a survey in Japan among physicians and laypeople found that even if patients had sufficient information regarding a potential treatment, there was still a difference in judgements between patients and physicians due to different perspectives of the importance of medical information [ 65 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is illustrated by an online survey with open questions among 592 patients and relatives in the Netherlands which found that following the patient’s, as well as relatives’ wish, was commonly mentioned to describe appropriate care [ 64 ]. It was also notable that it can be considered appropriate when patient or family/guardian understands that a treatment is unlikely to succeed but chooses to attempt a curative or life-prolonging treatment anyway [ 64 66 ] ( n = 3). For instance, a survey in Japan among physicians and laypeople found that even if patients had sufficient information regarding a potential treatment, there was still a difference in judgements between patients and physicians due to different perspectives of the importance of medical information [ 65 ].…”
Section: Resultsmentioning
confidence: 99%
“…Adding complexity is the consideration of resource consumption and economic burden to the healthcare system [ 66 , 68 , 76 , 89 , 90 ]. This relates to contexts involving staff burnout and moral distress [ 75 , 91 94 ] that have been demonstrated to accompany decisions to treat when little or no hope of benefit exists.…”
Section: Discussionmentioning
confidence: 99%
“…Much may be said for experience. Indeed, some studies suggest that seniority of staff boosts chances of survival, but careful assessment of all possible variables remains key 6 7. Additionally, before we prognosticate, we must consider all potential (including aggressive) treatments.…”
Section: Definition Of Comamentioning
confidence: 99%
“…When compared with the fellows, the attending physicians were more accurate in their predictions and able to offer more reasons to support their assessment that treatment was futile. 39 One area on which many clinicians agree is that medical practices often are dictated by fears of litigation, which can greatly impact EOL decision making. Though legislation exists regarding medical futility and decision-making processes, clinicians still believe there is a lack of support.…”
Section: Problems With Futilitymentioning
confidence: 99%